Study of foramen openings and their concurrence with root apexes - Sandra Maria Alves SAYÃO MAIA; Ana Paula Peres COSTA; Ana Tereza de Albuquerque LEMOS; Valeska Rodrigues Jacob TORRÃO; Ana Virginia Silva VILELA (Revista Sul-Brasileira de Odontologia, 2006)
The present study is aimed at evaluating the anatomic concurrence between foramen openings and root apexes of 247 upper and lower permanent human molar canals, the distance between these structures, the instrument that best fits into the root canal, as well as the direction of foramen deviation. Sixty-four of the canals were partially impenetrable and were discarded. The findings showed that 39.9% of the root canals studied had their apical foramen concurrent with their root apexes and 60.1% did not. Clinicians must be made aware of this important anatomical detail, which could be indispensable for successful endodontic treatment.